2013
DOI: 10.3389/fimmu.2013.00225
|View full text |Cite
|
Sign up to set email alerts
|

Ly9 (CD229) Cell-Surface Receptor is Crucial for the Development of Spontaneous Autoantibody Production to Nuclear Antigens

Abstract: The Signaling Lymphocyte Activation Molecule Family (SLAMF) genes, which encode cell-surface receptors that modulate innate and adaptive immune responses, lay within a genomic region of human and mouse chromosome 1 that confers a predisposition for the development of systemic lupus erythematosus (SLE). Herein, we demonstrate that the SLAMF member Ly9 arises as a novel receptor contributing to the reinforcement of tolerance. Specifically, Ly9-deficient mice spontaneously developed features of systemic autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…A recent study has shown that Ly9 (SLAMF3)-deficient mice develop spontaneous autoimmunity, and that in vitro anti-CD3-and anti-CD28-stimulated CD4 + T cells from Ly9-deficient mice exhibit greater IFNγ production compared with their wild type counterparts, suggesting SLAMF3 involvement in protection against autoimmunity (9).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that Ly9 (SLAMF3)-deficient mice develop spontaneous autoimmunity, and that in vitro anti-CD3-and anti-CD28-stimulated CD4 + T cells from Ly9-deficient mice exhibit greater IFNγ production compared with their wild type counterparts, suggesting SLAMF3 involvement in protection against autoimmunity (9).…”
Section: Discussionmentioning
confidence: 99%
“…Sle1b [ Sle1b ] and B6.1 29chr1b [129chr1b] develop autoantibodies linked to polymorphisms of SLAMF1-7 molecules (14) (15). SLAMF3-deficient mice (129xBALB/c) spontaneously develop autoimmune characteristics including autoantibodies against nuclear antigens, aberrant cytokine production and splenomegaly (16) and SLAMF1, 5 and 6 serve as negative regulators of humoral immune response (17). …”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in the Ly108/Slamf6 gene are implicated in the loss of early B cell (4) as well as peripheral T cell-mediated tolerance (5). Several independent studies have suggested the contribution of three other SLAMF genes, Slamf1 (SLAM/CD150), Slamf2 (CD48) and Slamf3 (Ly9) in autoimmunity (68). However, the role of B cell-intrinsic expression of different isoforms of Ly108 or other SLAM receptors in the regulation of B cell tolerance at the germinal center (GC) checkpoint remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Because Slamf genes are genetically linked, it has been difficult to determine the potential role of polymorphisms in a specific family member in autoimmunity using knockout mice generated in an autoimmune 129 background that are subsequently backcrossed to B6 (68, 12, 13). It is also unclear whether non- Slamf genes located in Sle1b contribute to a break in B cell tolerance given the presence of non-synonymous mutations in these genes in autoimmune B6.…”
Section: Introductionmentioning
confidence: 99%